New construction as a solution to jail overcrowding: Some policy and funding considerations - Orrick, David (American journal of criminal justice, 1989)
The problem of overcrowding in jails will not quickly go away. it is a safe prediction that there will be a trickle down effect on jail populations from increased incarcerations derived from gettough policies on drug offenders, for example. Whatever the reasons for overcrowding, the issue of new jail construction over the nation as a whole will be an on-going one, emphasizing the obvious valuein the sharing of information in the professional community. Those involved in the construction decisions must be alert to the long-term consequences of those construction decisions, and planning methods. It is one thing for the jail to stand there as a testimony to correctional architecture. It is every bit as important that everyone affected by the decisions appreciates what was involved, since the conceptual legacy of the (new) jail is ultimately just as important as the building itself.